(untitled) (The Peerian Journal, 2023)
The quest for happiness has intrigued humanity since ancient times, transcending eras, and garnering interest from thinkers across various civilizations. Recreational games derive significance from the importance of psychological well-being, serving as a human trait through which individuals express their thoughts, emotions, and sensations in diverse forms. The importance of recreational games offered to children during their formative years lies in the development of their mental and psychological processes, such as observation, attention, perception, and generalization.